Investigating Physical Aspects of Visual Communication in Mental Health Unit of Malaysia - Tan , Tihor; Syed Fadzil, Sharifah Fairuz (MAJ - Malaysia Architectural Journal, 2020)
Physical aspects of healing environment play a big and essential role in hospital design for creating an effective healing environment. The existing public mental health hospital in Malaysia is selected as the main case study to be reviewed in term of evidence-based physical aspects of healing architecture. Investigation mainly on the visual communication affecting the mental health unit has been carried out with methods understanding the current level of design implementation in Malaysia healthcare buildings. Many researchers have proven that physical aspects like space, lighting, color, privacy and communication have very huge impact on circadian rhythm and sleeping quality of mental health patients. The paper concluded with discussion on the impact of visual communication and by reviewing the current Malaysia mental health unit whether it achieved a certain standard of healing environment in term of physical aspects mainly of visual communication. Final analysis has been concluded after combining both the data from correlation analysis and structured interviews. The relationship of visual communication and healing environment is discussed for further recommendation based on this research objectives.